Penerapan Prinsip Citizenship (Peran Aktif Masyarakat) dalam Mitigasi Bencana Erupsi Gunung Marapi di Wilayah Agam Timur - Pratama, Haikal; Alhadi, Zikri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The application of the citizenship principle in disaster management emphasizes the active involvement of citizens in ensuring the safety and resilience of their regions through both direct participation and collaboration with the government. This study analyzes the implementation of citizenship in the mitigation of the Mount Marapi eruption in Agam, focusing on community participation and the responsiveness of the Regional Disaster Management Agency (BPBD). Using a descriptive qualitative method, data were collected through in-depth interviews with BPBD officials, village leaders, community figures, and affected residents, supported by policy documents and official reports. Findings indicate that communities actively participate in preparedness and response efforts, though challenges remain in terms of limited resources and weak inter-agency coordination. BPBD plays a key role in information dissemination and adaptive policy implementation. The study concludes that while citizenship-based mitigation is in progress, it requires further strengthening through capacity building, institutional coordination, and the integration of civic values in disaster policies.